PROPOSED INVENTORY CONTROL POLICIES FOR POWER PLANT COMPANY (CASE STUDY: PLTU BANJARSARI) - Dimas Fachri, Reynaldo
In 2021, PT BPI's financial condition has decreased which is caused by cash deficiency. It is happened because the company’s cash is used by creditors as collateral in the payment of the company's obligations (debts) as a result of the company's inability to pay its obligations in previous years. Another cause of this cash deficiency is because PLTU is not able to produce in accordance with the target, so the company is not able to generate revenue from the production optimally. This is proven by the cumulative Availability Factors (AF) value of PLTU Banjarsari in 2021 is still lower than the target due to high unplanned outage hours. The boiler is one of the most frequently disrupted parts and the highest producer of unplanned outage hours. If any part of the boiler is damaged, it is necessary to repair it which causes the plant unit to stop operating. If the plant unit stops/does not operate, the plant unit cannot generate electrical energy. So, to prevent that, it is necessary to carry out maintenance activities. To support good maintenance activities, the availability of spare parts needs to be considered. Because spare parts inventory has important roles to maintain the main component works properly. However, PT BPI's inventory cost in 2021 has been swelling due to the absence of an inventory policy that causes the absence of control in the provision of spare parts. Therefore, a spare parts inventory control policy is needed in terms of determining order quantity, reorder point, and safety stock. So, it is expected that the existence of a new inventory policy related to quantity orders, safety stocks, and reorder points will help the company to increase the cash flow. This study aims to find out and determine the appropriate inventory control policy related to determining the value of order quantity, reorder point, and safety stock to support Circular Fluidized Bed (CFB) boiler maintenance activities. Also, to find out how much inventory costs can be reduced after the implementation of the new inventory control policy. To develop solutions to inventory problems, it started by classifying each spare part using ABC Class-Based method to find out the criticality and desired service level. The 10spare part of CFB Boiler have high service level ranged from 87%–97%. Based on spare part demand pattern classification, the 10 spare parts have a lumpy demand pattern. So, the appropriate forecasting method that suit this type of demand pattern in Croston-Syntetos & Boylan Approximation method. The forecasting results show that forecast values are accurate and resemble with the historical data. This is proven by the low value of forecast error testing (MAD, MSE, MAPE, and SMAPE). Then the Probabilistic Economic Order Quantity (PEOQ) inventory control model is used to determine the value of safety stock, reorder point, and order quantity by using the forecasting result data. By applying the PEOQ method, the Total Inventory Annual Cost value can be reduced by IDR 156.337.533.14 or around 13.5%. This value decreased from the previous IDR 1,157,876,687.77 to 1,001,539,154.63. In addition, the results of the application of the PEOQ method can make spare part orders on time, and overstock and out of stock in the warehouse can be minimized.